The Development of Authentic Assessment Instruments on Anecdotal Text Material for Class X Students of SMK Yapim Indrapura, Batu Bara Regency - Lita Sentiana Hutapea; Malan Lubis; Abdurahman Adisaputera (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The learning process and assessment instruments provided do not cover three authentic domains in the 2013 curriculum. This study aims to describe the process of developing an authentic text assessment tool to describe the process of developing authentic assessment instruments on anecdotal text material for class X students of SMK Yapim Indrapura, Batubara Regency; describe how the appropriateness of authentic assessment instruments on anecdotal text material; and describe how effective authentic assessment instruments are on anecdotal text material. This study refers to the Borg & Gall development model. The results showed that: (1) development of authentic assessment instruments on anecdotal text material based on research and preliminary information collection, planning, initial product development, design validation and evaluation, product revisions, assessments and suggestions of language teachers and students, revisions, individual trials, revisions, small group trials, revisions, limited field trials, revisions until the product is valid and fit for use; and (2) the average percentage of all sub-components from the results of the material expert validation is 87% with "very good" criteria. The average percentage of all indicators from the results of expert evaluation validation for the multiple choice form instrument is 90.63%; for the description instrument is 89.54%; and for psychomotor instruments is 90%. All evaluation expert assessments are at criteria of "very good". The teacher response results have an average total percentage 96% with "very good" criteria. The results of student responses are declared feasible and meet needs, the total percentage is average 91.6% with the overall criteria of "very good".